A new species of Xeroderus Gray, 1835 (Phasmida: Phasmatidae: Xeroderinae) from Papua New Guinea and notes on the genus - Brock, Paul D.; Hennemann, Frank H. (Zootaxa, 2023)
Studies on the genus Xeroderus have revealed a new species from Papua New Guinea: Xeroderus conlei sp. n., which is described and figured from the holotype female only. Keys are provided to compare it with X. kirbyi Gray, 1835 from Australia, the only other species in the genus. Lectotypes are designated for X. kirbyi and the synonym Cooktownia plana Sjöstedt, 1918. Xeroderus brevipennis Redtenbacher, 1908 is found to be a member of Nisyrus Stål, 1877 and is here removed from Xeroderus and transferred to Nisyrus Stål, 1877. N. brevipennis (Redtenbacher, 1908) comb. n. is the first record of Nisyrus from the Solomon Islands. Various additional Australian localities are recorded for X. kirbyi Gray, 1835.